2016
DOI: 10.1097/dad.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features, p53, c-Kit, and Poliomavirus Status and Impact on Survival in Merkel Cell Carcinoma Patients

Abstract: We conclude that presence of MCPyV DNA has no effect on overall survival. MCCs with p53 and c-kit expressions are associated with the absence of or low MCPyV DNA showing an inverse relationship. A multifactorial molecular pathogenesis where positivity for p53 and c-kit are associated with other mechanisms different than MCPyV (such as pro-mitotic factors) may lead to aggressive clinical behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…From a clinical standpoint, male gender, tumor location on the head and neck, large tumor diameter, immunosuppression, and lymph node involvement correlate with a worse prognosis for MCC. 17 From a histopathologic standpoint, lymphovascular invasion (detected on routine sections or with D2‐40 staining), positive staining for p63, and higher mast cell counts are poor prognostic indicators for MCC, while infiltration of the tumor by CD8+ lymphocytes has been found to indicate favorable prognosis . The detection of polyomavirus has been found to be a marker of favorable prognosis in some studies, but other studies have not found this association …”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, male gender, tumor location on the head and neck, large tumor diameter, immunosuppression, and lymph node involvement correlate with a worse prognosis for MCC. 17 From a histopathologic standpoint, lymphovascular invasion (detected on routine sections or with D2‐40 staining), positive staining for p63, and higher mast cell counts are poor prognostic indicators for MCC, while infiltration of the tumor by CD8+ lymphocytes has been found to indicate favorable prognosis . The detection of polyomavirus has been found to be a marker of favorable prognosis in some studies, but other studies have not found this association …”
Section: Discussionmentioning
confidence: 99%
“…47,48 Parameters such as lymphovascular invasion, p53 and p63 immunopositivity, increased mast cell concentration, and vascular density as determined by CD34 staining have been implicated as factors that negatively affect MCC survival. [49][50][51][52][53][54] Lymphovascular invasion can be detected by immunostaining with D2-40 or CD31. 55 Prior MCC literature has demonstrated the prognostic potential of tumor-infiltrating lymphocytes (TIL).…”
Section: Diagnosis Staging and Prognostic Markersmentioning
confidence: 99%
“…Weitere prognostische Marker mit negativem Effekt auf das Überleben stellen Tumorgröße, eine p53- und p63-Immunpositivität, eine lymphovaskuläre Infiltration, eine erhöhte Mastzellkonzentration und eine Erhöhung des Endothelzellmarkers CD34 in der Immunhistochemie dar 30 , 31 , 32 , 33 .…”
Section: Staging Und Prognostische Markerunclassified